Cytological alterations and oxidative stress induced by Cerium and Neodymium in lentil seedlings and onion bulbs - Gjata, Isidora; Tommasi, Franca; De Leonardis, Silvana; Dipierro, Nunzio; Paciolla, Costantino (Frontiers in Environmental Science, 2022)
Rare earth elements (REEs) are a group of 15 elements, the lanthanides and Yttrium and Scandium, with similar chemical and physical properties. Their use for many advanced technological applications remarkably increased in the last decades, and it was associated with an intensive extraction of such elements from their ores. Consequently, increasing amounts of either REE-containing by-products, deriving from the extraction process, and REE-containing wastes, deriving from the disposal of REE-containing devices, are reaching the environmental systems both at the local and global levels, as never in the past. Few data in the literature concern the effect (beneficial or toxic) induced by REEs application in terrestrial plant species and at different physiological stages. A set of experiments with exposure to two REEs was performed on some plants to evaluate this. Data of investigations focused on the exposure of lentil (Lens culinaris Medik.) seedlings and onion (Allium cepa L.) bulbs to cerium chloride (CeCl3) and neodymium chloride (NdCl3) at different concentrations for 72 hours. Results showed alteration of the growth rate and the levels of some parameters considered as biomarkers of stress (reactive oxygen species and antioxidant systems). An increase in some mitotic aberrations was also observed in the root tissues of both species. The results indicate that the sensitivity of lentil in this bioassay is higher for lower concentrations compared to onion. Also, lower concentrations of these REEs had a positive effect on the growth rate of lentils underlining the complex interaction occurring between REEs and different plant organisms.